A novel process for volatile fatty acids production from syngas by integrating with mesophilic alkaline fermentation of waste activated sludge. (1st August 2018) - Rao, Yue; Wan, Jingjing; Liu, Yafeng; Angelidaki, Irini; Zhang, Shicheng; Zhang, Yalei; Luo, Gang
Abstract: The present study proposed and demonstrated a novel process for the bioconversion of syngas (mainly CO and H2 ) to valuable volatile fatty acids (VFA) by integrating with mesophilic alkaline fermentation of waste activated sludge (WAS). The results showed that although pH 9 was suitable for VFA production from WAS, 62.5% of the consumed CO was converted to methane due to the presence of hydrogenogenic pathway for CO conversion. The increase of pH from 9 to 9.5 inhibited the methane production from CO because of the possible presence of only acetogenic pathway for CO conversion. However, methane was still produced from H2 contained in syngas through hydrogenotrophic methanogenesis, and around 32–34% of the consumed syngas was converted to methane. At both pH 9 and 9.5, methane was produced by hydrogenotrophic methanogens Methanobacteriales . Further increase of pH to 10 effectively inhibited methane production from syngas, and efficient VFA (mainly acetate with the concentration of around 135 mM) production by simultaneous conversion of syngas and WAS was achieved. High acetate concentrations (>150 mM) were shown to have serious negative effects on the conversion of syngas. The addition of syngas to the mesophilic alkaline fermentation of WAS at pH 10 not only resulted in the enrichment of some known bacteria related with syngas conversion, but also changed the microbial community compositions for the fermentation of WAS. Graphical abstract: Highlights: PH 10 was crucial for simultaneous VFA production from WAS and syngas. Hydrogenotrophic methanognesis occurred even at pH 9.5 Hydrogenogenic pathway for CO conversion was suppressed at pH 10. Microbial community degrading WAS was changed upon the addition of syngas.